Money, culture, and well-being in Rome's economic development, 0-275 CE - Hoyer, Daniel, 1982- (Mnemosyne, Supplements, 2018)
The Roman Empire has long held pride of place in the collective memory of scholars, politicians, and the general public in the western world. In Money, Culture, and Well-Being in Rome's Economic Development, 0-275 CE , Daniel Hoyer offers a new approach to explain Rome's remarkable development. Hoyer surveys a broad selection of material to see how this diverse body of evidence can be reconciled to produce a single, coherent picture of the Roman economy. Engaging with social scientific and economic theory, Hoyer highlights key issues in economic history, placing the Roman Empire in its rightful place as a special-but not wholly unique-example of a successful preindustrial state.